Integrable superconductivity and Richardson equations - Belokolos, E.D. (Український математичний журнал, 2007)
For the integrable generalized model of superconductivity a solution of the Richardson equations for a spectrum of model is studied. For the case of narrow band the solution is presented in terms of the generalized Laguerre or Jacobi polynomials. In asymptotic limit, when the Richardson equations are transformed to an integral singular equation, the properties of an integration contour are discussed and a spectral density is calculated. Conditions for appearance of gaps in the spectrum are considered. Для інтегровної узагальненої моделі надпровідності досліджено розв'язання рівнянь Річардсона для спектра моделі. У випадку вузької зони розв'язок подано в термінах узагальнених поліномів Лагерра та Якобі. В асимптотичному випадку, коли рівняння Річардсона трансформуються в інтегральне сингулярне рівняння, з'ясовано властивості контура інтегрування та розраховано спектральну щільність. Розглянуто умови появи щілин у спектрі.